1973
DOI: 10.1159/000102857
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Drug-Induced Parkinsonism

Abstract: Three non-schizophrenic individuals with drug-induced parkinsonism of a prolonged nature were presented. This is the first report of the occurrence of this extrapyramidal side effect in patients without a diagnosis of psychosis and demonstrates that neuroleptic-induced parkinsonism can occur in such individuals. The prolonged nature of the disability following withdrawal was unusual. Although such occurrences have been previously reported, no long-term study of the natural history of this syndrome has been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(22 citation statements)
references
References 9 publications
1
20
0
1
Order By: Relevance
“…Most notably, our cases recovered gradually from severe EPS several months after cessation or reduction of neuroleptics, in agreement with some early case reports showing sustained but reversible parkinsonism [9]. Klawans et al [6] described initially such neurotoxic effects of neuroleptics as ''prolonged'' drug-induced parkinsonism. However, the clinical picture of the cases reported here is apparently different from those reported by Klawans et al [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most notably, our cases recovered gradually from severe EPS several months after cessation or reduction of neuroleptics, in agreement with some early case reports showing sustained but reversible parkinsonism [9]. Klawans et al [6] described initially such neurotoxic effects of neuroleptics as ''prolonged'' drug-induced parkinsonism. However, the clinical picture of the cases reported here is apparently different from those reported by Klawans et al [6].…”
Section: Discussionsupporting
confidence: 91%
“…Klawans et al [6] described initially such neurotoxic effects of neuroleptics as ''prolonged'' drug-induced parkinsonism. However, the clinical picture of the cases reported here is apparently different from those reported by Klawans et al [6]. The clinical picture described by Klawans et al showed a simple sustained parkinsonism, but our cases showed a wide spectrum of EPS (e.g., severe rigidity in limited body areas and with coexistence of oral dyskinesia).…”
Section: Discussionmentioning
confidence: 99%
“…However, usually it takes weeks to many months before drug-induced parkinsonism remits after the discontinuation of neuroleptics. 26 Indeed, drug-induced parkinsonism usually improves slowly over time with reduction or cessation of the offending drug. 27 Recently, Mirsattari et al described six patients with HIV infection and parkinsonism in whom the interruption of neuroleptics produced complete recovery in only one patient (2 months later) and partial or no response in others.…”
Section: Discussionmentioning
confidence: 99%
“…[67][68][69] In a French elderly cohort of 2,991 noninstitutionalized individuals, neuroleptic exposure increased 3.2-fold the risk to develop probable PD. 70 The risk was significant for benzamides and the calcium channel blockers flunarizine and cinnarizine.…”
Section: Other Clinical Issues Persistent Parkinsonism Following Neurmentioning
confidence: 99%